T-cell killing of target cells induced by hybrid antibodies: comparison of two bispecific monoclonal antibodies. - Clark, MR; Waldmann, H (1987)
Two different bispecific hybrid antibodies were generated by cell fusion of pairs of existing hybrid-myeloma cell lines. Both hybrid antibodies had similar specificity for human CD3 and mouse Thy-1 but differed in the isotypes of the immunoglobulin heavy chains. Hybrid HA2b/2b was a hybrid between a rat IgG2b (CD3) and a rat IgG2b anti-Thy-1, whereas HA2b/2c was a hybrid between the same rat IgG2b (CD3) and a rat IgG2c anti-Thy-1. Both hybrid antibodies were found to be very potent in inducing the killing of Thy-1-positive targets by human T-cell blasts, with the hetero-hybrid HA2b/2c showing a higher titer. T-cell blasts generated from resting peripheral blood mononuclear cells by a novel mitogenic antibody, YTH361, were exploited as effector cells. In addition to the CD3-dependent killing, the rat IgG2b anti-Thy-1 antibody and the hybrid antibody HA2b/2b but not the rat IgG2c anti-Thy-1 or the hybrid antibody HA2b/2c were also able to elicit antibody-dependent cell-mediated cytotoxicity (ADCC). This ADCC was inhibited by an anti-FcRlow (CD16) monoclonal antibody, which suggests that these effectors were K-cells. Toxicity toward the T-cell blast effector population was also observed, but in this instance the hetero-hybrid HA2b/2c had a lower cytotoxic titer. In conclusion, mixed isotype hybrid antibodies may have some advantages for eliciting T-cell-mediated killing of tumor cell targets by exhibiting a better therapeutic ratio of target cell to effector cell cytotoxicity.